UPLC-MS/MS assay for quantification of an inhibitor of kinases (Foretinib) in plasma: Application to a pharmacokinetic study in rats - Essam Ezzeldin; Muzaffar Iqbal; Yousif A. Asiri; Azza A. Ali; Toqa El Nahhas (Elsevier, 2020)
Foretinib, an oral multikinase inhibitor, is known to have anti-tumor effects against cancers. The doses and the levels of foretinib vary based on the type of cancer to be treated. An accurate and precise method is required to determine the level of foretinib and its pharmacokinetics. Here, we developed such a method, which was validated based on the guidelines of the FDA and EMA. Foretinib and ibrutinib (the internal standard (IS)) were extracted using tert-butyl methyl ether. Foretinib and IS were eluted in approximately 1.2 min. Thus, a linear, fast, accurate, and precise method was developed. The calibration curve was linear (r2 ˃ 0.997) in the range of 0.5-400.0 ng/mL and the lowest limit of quantitation was 0.5 ng/mL. The average recovery, accuracy, and precision were 87.9%, 88.7%, and ≤7.8%, respectively. The analyte was deemed stable using various stability tests. The validated assay was then fruitfully applied to a pharmacokinetics study in rats, which revealed that foretinib was absorbed and the maximum concentration achieved at 4.0 h after the administration of a single dose of foretinib. Keywords: UPLC-MS/MS, Foretinib, Pharmacokinetic, Rats, Ibrutinib